Predictors of Response to (Etanercept) in the Treatment of Iraqi Patients with Active Rheumatoid Arthritis - Jassim, Nizar A. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Since the introduction of tumour necrosis factor-alpha (TNF-α) inhibitors including etanercept, their efficacy and safety in treatment of rheumatoid arthritis (RA) have been studied in many randomized controlled clinical trials. However, data regarding predictors of clinical response to anti-TNF therapy are still sparse.Objective: To assess the predictors of response to etanercept in treatment of Iraqi patients with active RA.Methods: An open label single group prospective study was conducted over 15 months on 190 Iraqi patients with RA. All the included patients were given etanercept at a dose of 50 mg by subcutaneous injection ona weeklybases. Each patient was followed at regular intervals of baseline,1, 3 and 6 months for disease activity using Disease Activity Score 28 (DAS28). Also we assess six different patients characteristics (age, gender, disease duration, the presence of rheumatoid factor, smoking status and the concomitant use of methotrexate) as predictors to etanercept response.Results: Data analysis showed a significant improvement in DAS28 with etanercept use over a period of 6 months. Females were more respondent to treatment than males. The concomitant use of methotrexate showed highly significant correlation with the treatment response. The other variables had no significant effect on response to treatment.Conclusion: Female gender and concomitant use of methotrexate have a significant correlation with response to etanercept treatment.